Work Environment's Impact on Student Self-Regulation in Learning: Dampak Lingkungan Kerja terhadap Regulasi Diri Siswa dalam Belajar - Pratiwi, Yesica Erika Putri Ade; Hariyanto, Wiwit (Indonesian Journal of Law and Economics Review, 2024)
This study examines the self-regulation practices of accounting students at Muhammadiyah College of Sidoarjo who work while studying, focusing on their transition from online to offline learning. Using qualitative methods, including interviews, observations, and documentation, the research found that students with flexible work conditions manage their study time better and have stronger self-regulation skills. In contrast, those in inflexible work environments struggle with self-regulation, often handling study tasks spontaneously. These findings highlight the need for targeted support to enhance the self-regulation skills of working students, especially those in rigid job conditions. Highlight: Flexible jobs improve students' self-regulation and study management. Inflexible jobs result in poor self-regulation and spontaneous studying. Targeted support needed for students in rigid work conditions. Keyword: Self-regulation, working students, offline learning, online learning transition, qualitative study